Global burden and epidemic trends of chronic kidney disease attributable to high body mass index: insights from the Global Burden of Disease Study 2021 - Zehui Rao; Kaihong Wang; Kun Zhou; Yuanyuan Duan; Yida Zhang (Renal Failure)
Background High body mass index (BMI) is associated with an increased risk of chronic kidney disease (CKD). However, studies on the CKD burden due to high BMI are limited.Methods This research uses data from the Global Burden of Disease (GBD) study to analyze the epidemiological characteristics of CKD due to high BMI from 1990 to 2021, including mortality rate and disability-adjusted life years (DALYs). Age-standardized mortality rate (ASMR) and age-standardized DALY rate (ASDR) were calculated, with stratified analyses by sex, age, and socio-demographic index (SDI) regions. The estimated annual percentage change (EAPC) assessed the trends over 32 years, and a Bayesian age-period-cohort (BAPC) model predicted the disease burden for the next 15 years.Results In 2021, the ASMR and ASDR for CKD attributable to high BMI globally were estimated at 5.06 [95% uncertainty interval (UI): 2.70–7.51] and 122.08 (95% UI: 66.25–180.18) per 100,000 population, respectively. Significant variations in these metrics were observed across sex, age groups, and regions. Between 1990 and 2021, both ASMR and ASDR exhibited an upward trajectory, with projections indicating a continued rise through to 2040.Conclusions Our findings indicate that the CKD burden due to high BMI is increasing, with notable disparities across sex, age, and geographic regions. Targeted public health interventions, particularly those focusing on males and older adults, are essential to address this growing health challenge.